Pengaruh Financial Leverage Terhadap Keputusan Investasi dengan Growth Sebagai Variabel Moderasi - , Christine Novanti Bayu; , Prof. Dr. Sukmawati Sukamulja, MM ([Yogyakarta] : Universitas Gadjah Mada, 2012)
In order to continue growing, a firm should invest, whereas this investment requires fund that can be acquired by internal or external financing. Internal financing is acquired from operating activity. External financing could be generated from debt (financial leverage) or issue new stock. Debt gives both positive and negative impact. Thus a firm should make leverage decision carefully in order not to restrain the investment. This research aims to test the impact of financial leverage to investment decision using growth as a moderating variable. This research uses sample consist of 130 firms listed on Indonesian Stock Exchange (IDX) period 2003 â 2007. This sample forms a panel data and processed using three models: pooled regression, fixed effect, and random effect. Those three models would go through further tests to choose the appropriate model, and the result is fixed effect model using crosssection weight. This model consists of investment decision as a dependent variable that is affected by cash flow, Tobinâs Q, leverage, and sales as independent variables, and growth as a moderating variable. This research is powerless to prove the impact of financial leverage to investment decision and growth is not moderating that relationship. It means that growth does not strengthen or weaken the relationship between financial leverage and investment decision. In other word, this research cannot prove whether the impact of leverage is stronger on low growth firms than on high growth firms. This research proves that factors affecting investment decision are cash flow, Tobinâs Q, and sales. It is in line with pecking order theory states if a firm needs fund, it will use internal financing derived from operating activity first. Suppose the internal fund is inadequate, then the firm will use external financing started from safe securities such as bond. Finally if it still inadequate, then the firm will issue new stock.